Maylan and his toy top - Lee, Marcy Dans (Quezon City Adarna House, Inc., 2013)
Maylan found a toy top buried in the sand. Little did he know that this top would cause quite a catastrophe in Langit, Lupa, and Ugsuban, and send Maylan to the horizon.
This book is recommended for children ages 11 and above.
Keywords: Children's stories, Philippine (English).